Gelation behavior of wheat gluten by heat treatment followed by transglutaminase cross-linking reaction - Wang, Jin-Shui; Zhao, Mou-Ming; Yang, Xiao-Quan; Jiang, Yue-Ming; Chun, Cui (Food hydrocolloids, 2007)
Improvement in the functional properties of food proteins using microbial transglutaminase (TGase) has been the subject of recent studies in food field. However, changes in functional properties of wheat gluten as affected by cross-linking with TGase have not been well studied. Gelation of wheat gluten treated by TGase was investigated in this present study. Obvious decrease in the minimum concentration for gelation of the heated gluten (16%) was found compared with 22% of the original gluten. The surface lysine and glutamine residues of the gluten increased with heating, the formation of ε- ( γ-glutamyl)lysyl cross-links increased markedly in the gelation of heated-gluten treated by TGase. Significant ( P < 0.05 ) improvements in rheological properties, water-holding capacity and texture properties of the TGase-induced gluten gels were observed, particularly, for gels of TGase-induced glutens treated by pre-heating. It indicated that TGase had significant ( P < 0.05 ) effect on gelation capacity and gel properties of wheat gluten proteins.